Utilización de abonos orgánicos (gallinaza y humus) en el cultivo de col (Brassica oleracea var. Capitata en el cantón Gonzanamá - Guamán Paladines, José Luis (2023)
In agriculture, an increase in production costs has been observed due to the use of chemical fertilizers, coupled with the contamination of food, the environment, water sources, and the degradation of soils, making them less productive over time. For this reason, the use of organic fertilizers is considered as an option that contributes to the improvement of soil's physical and chemical structures, offering sustainable benefits for farmers and society. The present research was conducted with the aim of evaluating the efficiency of two types of organic fertilizers (chicken manure and humus) in the cultivation of cabbage (Brassica Oleracea Var. Capitata) at "Piedra Grande" farm, located in the Nambacola parish, Gonzanamá canton. A completely randomized design (CRD) was used, consisting of four treatments: T1 (Chicken manure), T2 (Humus), T3 (Mixture of chicken manure + humus), and T4 (Control), with three replicates per treatment, resulting in a total of 12 experimental units. The research was conducted over a period of 32 days. Among the treatments, T1 (Chicken manure) showed higher values in stem diameter (1.04cm), root length (4.80cm), leaf count (10), 0.0% plant mortality, and plant weight (132.68g). It should be noted that the T1 treatment (chicken manure) is a good organic fertilizer that is recommended for use due to its significant contribution of nutrients to the soil. Keywords: agriculture, pollution, organic fertilizer, improvement, soil structure.